FACTORS AFFECTING SLEEP PATTERN OF PREGNANT WOMEN IN 3rd TRIMESTER - R. Bondad; Z. Abedian (نشریه پرستاری ایران, 2004)
One of the most common Compliant of pregnancy is sleep disturbances. Producing factors of sleep disorders are different, in such away that cause many hardships in pre, Para and post partum. So, assessing sleep pattern in 3rd trimester of pregnancy, we conducted a descriptive research on 320 pregnant women. Data related to their sleep pattern were collected through sleep-log scale, and other required information's were gathered by interview sessions. As the results showed means of scores related to total sleep, quality of sleep, insomnia and finally alertness in daytime were respectively 26.05 8.76, 7.72 3.89, 12.87 4.86 and 5.46 3.05. Moreover, the most common probable reasons of sleep disturbances were urinary frequency (56.3%), back pain (48.1%), turning to sides (32.8%), mental engagements (30.6%) fetal movement (30.3%) and heart burn (29.1%). Overall, since many pregnant women suffer from sleep disturbances, especially during 3rd trimester, it is recommended to provide support systems to take care of mental health of mothers. Preventing side effects of sleep disturbances will promote mother and fetal well being.